Radioguided Parathyroidectomy with Portable Mini Gamma-Camera for the Treatment of Primary Hyperparathyroidism. (15th September 2015) - Casella, Claudio; Rossini, Pierluigi; Cappelli, Carlo; Nessi, Chiara; Nascimbeni, Riccardo; Portolani, Nazario
Abstract : Background . A proper localisation of pathological parathyroid glands is essential for a minimally invasive approach in the surgical treatment of primary hyperparathyroidism (PHP). The recent introduction of portable mini gamma-cameras (pMGCs) enabled intraoperative scintigraphic scanning. The aim of our study is to evaluate the efficacy of this new method and compare it with the preoperative localisation surveys. Methods . 20 patients were studied; they were evaluated preoperatively by neck ultrasound andTc 99mm -sestaMIBI-scintigraphy and intraoperatively with the pMGC IP Guardian 2. The results obtained from the three evaluations were compared. Results . The pMGC presented a sensitivity of 95%, a specificity of 98.89%, and a diagnostic accuracy of 98.18%, which were higher than those of preoperative ultrasound (sensitivity 55%; specificity 95%; diagnostic accuracy 87%) and scintigraphy withTc 99mm -sestaMIBI (sensitivity 73.68%; specificity 96.05%; diagnostic accuracy 91.58%). Conclusions . The pMGC can be used effectively as an intraoperative method to find the correct location of the pathological parathyroid glands. The pMGC is more reliable than the currently used preoperative and intraoperative localisation techniques.